EXPLORING MOTHER'S HEALTHY FEEDING PRACTICES OF CHILDREN, AGES 4-6 YEARS: A QUALITATIVE STUDY - Anita Rahmiwati; Ditia Fitri Arinda; Feranita Utama; Misnaniarti (Faculty of Public Health, Sriwijaya University, 2019)
Background: Feeding or eatinggood upbringing which affects the development growth and intelligence of children. For that, it is necessary for feeding patterns or parenting eat right and balanced in order to stay healthy and avoid infection or other diseases related to nutrition. A balanced diet is eating according to the composition of food that our body needs in portions adapted to the needs of children at each age. Methods: Respondents in this study are the parents of kindergarten children Rabbani North Indaralaya with a range of aged 4-6 years. Implementation of FGD was attended by 12 people, consisting; three researchers, two minutes, and seven respondents. Respondents selected through purposive sampling,based on predetermined criteria and is considered capable of answering research problems. The purpose of the study is to explore more deeply about parenting feeding mothers in Ogan Ilir associated with understanding (the concept of balanced nutrition, quantity of feeding practices in terms, frequency, form, variety, and type of food). This study used a qualitative approach. The data collection technique is Focus Group Discussion. Data processing was done manually using the content analysis method (analysis). Results: The results showed majority of mothers do not understand that concept of balanced nutrition, for this aspect the number of feeding infants in Ogan Ilir still do not meet the nutritional needs to children as seen from the children often do not prepare food to consume by their mother if the child does not as the dishes served. From the aspect of the frequency, almost mothers only give meal 2-3 times and one times an additional food during the day. From this aspect of a mother, a form has given the same food with family to meal, but this menu gives only food in like a child. In terms of variety of food provided to children are still less, and most children do not consume vegetables and fruit.Conclusions:Mother feeding patterns in children are not good, lack of parental support in providing food resulted in children accustomed to eating that is not good. Appropriate educational media is the required age of children to increase the child's knowledge about nutritious food and motivate children to want to eat nutritious food.